Assessment of validity and reliability of Kvaal's method for age estimation among a population sample - A retrospective study - Prashant Kumar Chandan; Karandeep Singh Arora; Mayank Das; Prabhpreet Kaur; Shreeyam Mohaptra; Shubhangi Pareek (Wolters Kluwer Medknow Publications, 2020)
Objectives: The present research was carried out with an aim to estimate and correlate chronological age and estimated age by Kvaal's Method in North Indian population using digital panoramic radiography. Further, the study was an attempt to evaluate the reliability of Kvaal's method for age estimation and to arrive at a population-specific regression equation. Materials and Method: One hundred digital orthopantomograms of participants aged between 20 and 70 years of age were selected. The evaluation of 6 teeth according to Kvaal's method was carried out using measure tool of Sidexis Software (provided by the manufacturer). Correlation coefficient was carried out between chronological age and estimated age and further regression analysis was carried out for obtaining a population specific regression equation. Results: It was observed that coefficient of determination (R2) is highest (0.223) for mandibular canine which indicates that age can be better estimated with this particular tooth. Conclusion: It was observed that large variations between the chronological and estimated age were not found. Also, Kvaal's formula proved accurate for estimating age using all the six selected teeth. Thus, it was concluded that mandibular canine would be the better tooth for age estimation, followed by maxillary second premolar and maxillary three teeth taken together.